Hydration layers trapped between graphene and a hydrophilic substrate - M Temmen; O Ochedowski; M Schleberger; M Reichling; T R J Bollmann (New Journal of Physics, 2014)
Graphene is mechanically exfoliated on ${\rm{Ca}}{{{\rm{F}}}_{2}}$ (111) under ambient conditions. We demonstrate the formation of a several monolayer thick hydration layer on the hydrophilic substrate and its response to annealing at temperatures up to 750 K in an ultra-high vacuum environment. Upon heating, water is released, however, it is impossible to remove the first layer. The initially homogeneous film separates into water-containing and water-free domains by two-dimensional Ostwald ripening. Upon severe heating, thick graphene multilayers undergo rupture, while nanoblisters confining sealed water appear on thinner sheets, capable of the storage and release of material. From modeling the dimensions of the nanoblisters, we estimate the graphene/ ${\rm{Ca}}{{{\rm{F}}}_{2}}$ (111) interfacial adhesion energy to be $0.33± 0.13$ ${\rm{J}}\;{{{\rm{m}}}^{-2}}$ , thereby viable for polymer-assisted transfer printing.